Kajian Literatur Penerapan Strategi Branding bagi Kemajuan UMKM di Era Digital - Aristawidia, Ifah Bunga (Jurnal Manajemen dan Inovasi (MANOVA), 2018)
Brand has an important role which is as the identity of a business and shape the image in the minds of the community. Moreover, living in the current digital era is the time of the emergence of technology so that it can facilitate the activities of Micro Small Medium Enterprises (MSME), including in building brands. But the problem is the lack of awareness of MSME in building brands and only a few MSME in Indonesia use digital media. Therefore, it is expected that SMEs can raise awareness in building brands and be able to adapt to the maximum use of internet media so that MSME brands can be well known to the international market. Of the existing problems it is necessary to discuss the basic concepts of branding for MSME, MSME obstacles in implementing branding, the main key to building branding in the digital era, and strategies for building MSME branding. This study uses a qualitative descriptive method that is using literature studies taken through relevant books, journals, and websites. The results of this study indicate that branding strategy is very important to be implemented for the advancement of MSME and that with the existence of internet media it can be easier to implement branding strategies for MSME.